Probing the physical properties of the intergalactic medium using blazars. Issue 2 (14th September 2021) - Dalton, Tony; Morris, Simon L; Fumagalli, Michele; Gatuzz, Efrain
ABSTRACT: We use Swift blazar spectra to estimate the key intergalactic medium (IGM) properties of hydrogen column density (NHXIGM ), metallicity, and temperature over a redshift range of 0.03 ≤ z ≤ 4.7, using a collisional ionization equilibrium model for the ionized plasma. We adopted a conservative approach to the blazar continuum model given its intrinsic variability and use a range of power-law models. We subjected our results to a number of tests and found that the NHXIGM parameter was robust with respect to individual exposure data and co-added spectra for each source, and between Swift and XMM–Newton source data. We also found no relation between NHXIGM and variations in source flux or intrinsic power laws. Though some objects may have a bulk Comptonization component that could mimic absorption, it did not alter our overall results. The NHXIGM from the combined blazar sample scales as (1 + z ) 1.8 ± 0.2 . The mean hydrogen density at z = 0 is n 0 = (3.2 ± 0.5) × 10 −7 cm −3 . The mean IGM temperature over the full redshift range is log( T /K) =6.1 ± 0.1, and the mean metallicity is [ X /H] = −1.62 ± 0.04( Z ∼ 0.02). When combining with the results with a gamma-ray burst (GRB) sample, we find the results are consistent over an extended redshift range of 0.03 ≤ z ≤ 6.3. Using our model for blazars and GRBs, we conclude that the IGM contributes substantially to the total absorption seen in both blazar and GRB spectra.